The effect of demographic and perception of justice towards Special Voluntary Disclosure Program (SVDP): A case of individual tax payer in Terengganu - Ahmad Zamakhshari, Hasbullah (2022)
Tax compliance is an issue faced by all countries and is often discussed globally, including Malaysia. Low compliance rates require tax administrators to identify appropriate methods and ways to solve the issue. One of the Malaysian government's initiatives in overcoming the above problems is by introducing Special Voluntary Recognition Program (SVDP) which starts from 3 November 2018 until 30 September 2019. The government through the Inland Revenue Board of Malaysia (IRBM) targets one million taxpayers to participate in this program with an expected collection of RM 10 billion. However, after the program ended, only 286,428 taxpayers participated and the collection was only RM 7.8 billion, which was lower than initially expected. Studies need to be done to identify the causes of participation and collection not as initially expected. Therefore, this study was conducted to identify the relationship between factors such as race, gender, type of income, marital status and perception of justice with participation in PKPS. This study uses data from the responses to questions that have been sent to taxpayers in Terengganu. A total of 300 people were selected to answer the question and only 133 provided feedback while the remaining 167 did not provide any feedback. The data has been analyzed by using SPSS software and the results showed that only marital status and perception of justice had a significant relationship with participation in PKPS in Terengganu. With the findings, it is hoped that the government, including the IRBM, can work together to identify target groups and formulate strategies to increase tax compliance rates in Malaysia and especially in Terengganu.